The origins of bioethics remembering when medicine went wrong - Lynch, John (John Alexander), 1976- (Rhetoric and public affairs series., 2019)
"In this book, author John Lynch shows how three controversial experiments--the Tuskegee Syphilis Study, the Willowbrook Hepatitis Study, and the Cincinnati Total Body Irradiation Study--have been remembered and forgotten, and why their memorialization or their erasure matters today"--